Reverse causal relationship between periodontitis and shortened telomere length: Bidirectional two-sample Mendelian random analysis - Hu, Jiaxin; Song, Jukun; Chen, Zhu; Yang, Jing; Shi, Qianhui; Jin, Fuqian; Pang, Qiyuan; Chang, Xingtao; Tian, Yuan; Luo, Yi; Chen, Liming (Frontiers in Immunology, 2022)
Background Observational studies have demonstrated a link between shortened telomere lengths(TL) and chronic periodontitis. However, whether the shortened TL is the cause or the result of periodontitis is unknown.Therefore, our objective was to investigate a bidirectional causal relationship between periodontitis and TL using a two-sample Mendel randomized (MR) study. Methods A two-sample bidirectional MR analysis using publicly available genome-wide association study (GWAS) data was used. As the primary analysis, inverse variance weighting (IVW) was employed. To identify pleiotropy, we used leave-one-out analysis, MR-Egger, Weighted median, Simple mode, Weighted mode, and MR pleiotropy residual sum and outlier (MR-PRESSO). Results In reverse MR results, a genetic prediction of short TL was causally associated with a higher risk of periodontitis (IVW: odds ratio [OR]: 1.0601, 95% confidence interval [CI]: 1.0213 to 1.1002; P =0.0021) and other complementary MR methods. In the forward MR analysis, periodontitis was shown to have no significant effect on TL (IVW: p = 0.7242), with consistent results for the remaining complementary MR. No pleiotropy was detected in sensitivity analysis (all P>0.05). Conclusion Our MR studies showed a reverse causal relationship, with shorten TL being linked to a higher risk of periodontitis, rather than periodontitis shorten that TL. Future research is needed to investigate the relationship between cell senescence and the disease.